Neural correlates underlying impaired memory facilitation and suppression of negative material in depression - Zhang, Dandan (Sci Rep, 2016)
Previous behavioral studies demonstrated that depressed individuals have difficulties in forgetting unwanted, especially negative, event. However, inconsistent results still exit and the neural mechanism of this phenomenon has not been investigated. This study examined the intentional memory facilitation/suppression of negative and neutral materials in depression using Think/No-Think paradigm. We found that compared with nondepressed group, depressed group recalled more negative items, irrespective of either "Think" or "No-Think" instructions. Accordingly, the frontal N2 (reflecting voluntary memory inhibition) and parietal late positive component (LPC) (reflecting conscious recollection) showed deflection for negative items in depressed compared with nondepressed participants. On the one hand, the reduced N2 for negative "No-Think" items indicated that depressed individuals have low motivation to suppress negative items so intentional forgetting is less successful for mood-congruent events. On the other hand, the enhanced LPC for negative "Think" items suggested that negative memories are excessively revisited by depressed participants (compared with nondepressed ones) due to their mood-congruent and intrusive nature. Thus we demonstrated that depressed individuals show behavioral and ERP deviations from healthy controls for both voluntary suppression and conscious retrieval of negative memory; the two abnormalities of memory control together contribute to the difficulties in forgetting negative material in depression.